Saline stress effect on cowpea beans growth under biofertilizer correction - Ednangelo Duarte Pereira; Albanise Barbosa Marinho; Elísia Gomes Ramos; Chrislene Nojosa Dias Fernandes; Francisca Robevania Medeiros Borges; Jilson de Nazaré José Adriano (Bioscience Journal, 2019)
New strategies to increase growth and food crops productivity in saline soils are priorities in the research. The experiment was carried out in a pot to investigate the growth of cowpea cv. Canapu in response to saline stress under the correction of a mixed biofertilizer. Five irrigation water salinity levels and three doses of the mixed biofertilizer were tested, with four replicates at each level. The increase in salinity level resulted in reductions in stem diameter, leaves number, shoot biomass and roots. The mixed biofertilizer use was able to minimize the effect of salinity in all analyzed variables, improving the cowpea growth and development, protecting from saline stress negative impacts. In addition, the mixed biofertilizer use may be an option to improve crop growth and productivity in salt affected soils.